Hubungan Positif COVID-19 pada Wanita Hamil dengan Kejadian Persalinan Bayi Prematur di Rumah Sakit Umum Daerah Al-Ihsan Jawa Barat - Yora Ordellia Budiawati; Sadiah Achmad; Ferry Achmad Firdaus Mansoer (Bandung Conference Series: Medical Science, 2022)
Abstract. Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by the virus SARS COV-2. This disease spreads very quickly and brings its concerns to pregnant women because it can cause very serious complications, among others is premature delivery, This study aims to see whether there is a relationship between COVID-19 and preterm labor. The research design used is a Cross-Sectional Comparative design, using secondary data from medical records with a total of 196 mothers giving birth and the data were tested by Chi-Square test. This study showed that 20.41% of COVID-19 positive pregnant women gave birth to premature babies while COVID-19 negative pregnant women gave birth to 12.24% of premature babies with a P-Value of 0.164 (P>0.05). There is no relationship between COVID-19 and preterm labor in pregnant women at Al-Ihsan Hospital West Java. This result was obtained because many maternity mothers chose to give birth outside the hospital such as independent practice midwives or maternity clinics as well as PONED and other primary health facilities. Abstrak. Corona Virus Disease 2019 (COVID-19) adalah penyakit infeksi yang diakibatkan oleh virus SARS COV-2. Penyakit ini menyebar luas dengan sangat cepat dan membawa kekhawatiran tersendiri bagi ibu hamil karena dapat menyebabkan komplikasi yang sangat serius antara lain persalinan prematur. Penelitian ini bertujuan untuk melihat ada tidaknya hubungan antara COVID-19 dengan persalinan prematur. Rancangan penelitian yang digunakan adalah disain Cross Sectional Comparative, data yang digunakan adalah data sekunder dari rekam medik dengan total 196 ibu bersalin dan data diuji dengan uji Chi Square. Di dapatkan wanita hamil COVID-19 positif melahirkan sebanyak 20.41% bayi prematur sedangkan wanita hamil negatif COVID-19 melahirkan sebanyak 12.24% bayi prematur dengan hasil P Value 0,164 (P>0,05). Tidak terdapat hubungan antara COVID-19 dengan persalinan prematur pada wanita hamil di RSUD Al-Ihsan Jawa Barat. Hasil ini didapatkan karena banyak ibu bersalin yang memilih untuk bersalin di luar RS seperti bidan praktik mandiri atau klinik bersalin maupun PONED serta fasilitas Kesehatan primer yang lain.